(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
Properties of materials in microscale are different from those in bulk form. This article aims to presents the experimental studies of the electrical properties of Polypyrrole thin film doped in organic acid. Ten samples of Polypyrrole doped in organic acids thin films with different layers were prepared using the spin coating method applied on glass substrates. The electrical resistance of the thin film is measured as a function of film thickness and temperature. The resistance decreases as the thickness of the thin film increases. Resistivity and conductivity were also calculated. It was observed that the resistivity value of Polypyrrole doped in organic acids is relatively small which is in 10E-3 Ωm, thus making it a good conducting material. In terms of conductivity, the thinner is the film, the higher is its conductivity. Temperature starting from room temperature until 45 °C with 5°C of increment was applied. The resistance increases when the temperature increases, thus exhibit a positive temperature coefficient type of thermistor characteristic. The resistivity on the other hand rise as the temperature rise. Whereas, the conductivity decrease with the increment of temperature. Advances in thin film technology will allow the fabrication of PPy doped in organic acids material for various applications including electronics and sensors.